Fundamental Power of Social Media Interactions for Building a Brand and Customer Relations - Ionica Oncioiu; Sorinel Căpușneanu; Dan Ioan Topor; Attila Szora Tamaș; Alina-Georgiana Solomon; Tatiana Dănescu (Journal of Theoretical and Applied Electronic Commerce Research, 2021)
The spread of social networks and the high level of penetration of digital content and mobile devices have created a society in which consumers expect constant communication from companies. In addition, communication on social media is often accompanied by the hope of being able to interact on an equal footing. In this way, companies hope that the use of social networks will not only increase sales, but also increase attention, brand page traffic, and customer loyalty. The purpose of this study was to provide the grounds for identifying the correlations between the interactive potential of social media based on dialogue-oriented communication and the quality of relationships with online customers. To achieve this goal, an online questionnaire was used in which 604 respondents from Romania participated (204 social media managers and 400 online customers). The results of the study showed that it is particularly important for companies to understand the role of interactive communication in social media and to thus build a bridge between the orientation of communication towards dialogue and relationships with online customers. It was found that the correct use of social networks could also support the achievement of public relation (PR) objectives. In addition, this study has implications for the development of customer-oriented online communication strategies by Romanian companies.